2022
DOI: 10.3390/nu14194021
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gastric Myoelectric Activity with Dietary Intakes, Substrate Utilization, and Energy Expenditure in Adults with Obesity

Abstract: Obesity can modulate gastric myoelectric activity (GMA); however, the relationship of GMA with nutrient intakes and substrate utilization in adults with obesity is lacking. We examined the association of dietary intakes, energy expenditure, and substrate utilization with the GMA. Participants (n = 115, 18–60 y) were divided into healthy weight (HW, n = 24), overweight (OW, n = 29), obese (OB, n = 41) and morbidly obese (MO, n = 21). Two-day multi-pass 24 h recalls were conducted. The GMA was measured by multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Table 4 shows that there were insignificant differences between patients with ED who had a BMI greater than the median and those with a BMI less than the median. Previous reports from our research group indicated that patients with severe obesity have higher WL volumes than health controls, while patients with overweight and those with non-morbid obesity had insignificant differences regarding the WL volume [22]. The BMI range of the participants in this current study was in the overweight to non-severe obesity range.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Table 4 shows that there were insignificant differences between patients with ED who had a BMI greater than the median and those with a BMI less than the median. Previous reports from our research group indicated that patients with severe obesity have higher WL volumes than health controls, while patients with overweight and those with non-morbid obesity had insignificant differences regarding the WL volume [22]. The BMI range of the participants in this current study was in the overweight to non-severe obesity range.…”
Section: Discussionsupporting
confidence: 39%
“…The EGG electrodes were placed on the skin at three sites: (a) mid-clavicular line, approximately two inches below the left costochondral margin; (b) mid-clavicular line on the right side, two inches below the right costochondral margin; (c) midline between the xiphoid and umbilicus. The EGG procedures are detailed in previous studies [16,22].…”
Section: Measuring the Gmamentioning
confidence: 99%